Ментортсво в іт-сфері - Тарасов, Д. К. (ХНУРЕ, 2023)
In the modern IT industry, mentoring is becoming more and more popular and plays an important role in the development of talented professionals. Mentoring helps beginners get the necessary experience and knowledge from experienced workers, which allows them to grow as professionals and solve complex tasks more effectively. In this article, we will consider the features of modern mentoring in the IT sphere and its advantages for the qualitative development of talented specialists.